THE ROLE OF FORMATIVE ASSESSMENT IN IMPROVING ENGLISH LANGUAGE LEARNING (Ustozlar uchun, 2026)
Formative assessment has become an essential component of modern English language teaching, focusing on continuous feedback and learner development rather than solely measuring final achievement. This study investigates the impact of formative assessment strategies, including classroom questioning, feedback techniques, self-assessment, peer assessment, and reflective learning activities, on students’ language proficiency and motivation. Drawing on classroom observations and recent educational research, the study demonstrates that formative assessment enhances learner engagement, promotes self-regulated learning, and improves communicative competence. The findings provide practical recommendations for integrating formative assessment into English language classrooms to create a more supportive and effective learning environment.